Brokers in Participatory Urban Governance: Assembling Formal and Informal Politics - Martijn Koster (L'Espace Politique)
Participatory urban governance, with its focus on citizen representation and the equitable distribution of resources, has been implemented globally to deepen democracy. Some individuals position themselves as voluntary representatives, or brokers, between the state and their fellow citizens. In this article I analyse the increasingly important and largely informal roles of such brokers in participatory urban governance. Informed by my research in Brazil and the Netherlands, this article explores how brokers position themselves in administrative schemes and how they operate both in and out of officially sanctioned channels and institutions. In general, the scholarly debate on brokerage within participatory governance is divided into two arguments: first, an argument about neoliberal deregulation, which encourages the practices of active citizen-mediators, and second, an argument about modernization, which sees brokers as remnants of a clientelist political system. The first argument, mostly based on research in the global North, sees brokers as formal mediators, while the second, mostly based on studies in the global South, sees them as engaged in highly informal and personalized transactions. In this article, to bridge the existing divide between these arguments, I present an approach of brokers as ‘assemblers’, connective agents who actively bring together different government and citizen actors, institutions and resources while combining formal and informal politics.